PENGEMBANGAN DESAIN MICRO HOUSE DALAM MENUNJANG PROGRAM NET ZERO ENERGY BUILDINGS (NZE-Bs) - Permana, Asep Yudi; Wijaya, Karto; Nurrahman, Hafiz; Permana, Aathira Farah Salsabilla (Jurnal Arsitektur ARCADE, 2020)
Abstract: Energy efficiency is a top priority in design, because design errors that result in wasteful energy will impact operational costs as long as the building operates. The opening protection in the facade should be adjusted according to their needs, for optimum use of sky light. Inhibiting the entry of solar heat into the room through the process of radiation, conduction or convection, optimum use of sky light and efforts to use building skin elements for shading are very wise efforts for energy savings. House construction planning must be careful and consider many things, including: physical potential. Physical potential is a consideration of building materials, geological conditions and local climate. Related to the issue of global warming that occurs in modern times, climate is a major consideration that needs to be resolved.The purpose of building design, especially in residential homes aims to create amenities for its inhabitants. Amenities are achieved through physical comfort, be it spatial comfort, thermal comfort, auditory comfort, or visual comfort.Energy waste is also caused by building designs that are not well integrated and even wrong and are not responsive to aspects of function, and climate. This is worsened by the tendency of the designers to prioritize aesthetic aspects (prevailing trends). The issue of green concepts and energy consumption efficiency through the Net Zero-Energy Buildings (NZE-Bs) program from the housing sector as a response to tackling global warming is already familiar in Indonesia, although its application has not yet been found significantly. Green concepts offered by housing developers are often merely marketing tricks and are not realized and grow the responsibility of the residents to look after them. Due to the lack of understanding of the green concept, housing developers tend to offer more a beautiful and green housing environment, not the actual green concept.Keyword: Socio-culture, Energy efficiency, Energy consumption, Environment. The green conceptAbstrak: Efisiensi energi merupakan prioritas utama dalam disain, karena kesalahan disain yang berakibat boros energi akan berdampak terhadap biaya opersional sepanjang bangunan tersebut beroperasi. Pelindung bukaan pada fasade sebaiknya dapat diatur sesuai kebutuhannya, untuk pemanfaatan terang langit seoptimal mungkin. Penghambatan masuknya panas matahari kedalam ruangan baik melalui proses radiasi, konduksi atau konveksi, pemanfaatan terang langit seoptimal mungkin serta upaya pemanfaatan elemen kulit bangunan untuk pembayangan merupakan upaya yang sangat bijaksana bagi penghematan energi. Perencanaan pembangunan rumah harus cermat dan mempertimbangkan banyak hal, antara lain: potensi fisik. Potensi fisik adalah pertimbangan akan bahan bangunan, kondisi geologis dan iklim setempat. Terkait dengan isu pemanasan global yang terjadi pada masa modern ini, iklim menjadi sebuah pertimbangan utama yang perlu diselesaikan.Tujuan desain bangunan khususnya pada rumah tinggal bertujuan menciptakan amenities bagi penghuninya. Amenities dicapai melalui kenyamanan fisik, baik itu spatial comfort, thermal comfort, auditory comfort, maupun visual comfort.Pemborosan energi juga disebabkan oleh desain bangunan yang tidak terintegrasi dengan baik bahkan salah dan tidak tanggap terhadap aspek fungsi, serta iklim. Hal tersebut diperparah yang kecenderungan para perancang lebih mementingkan aspek estetis (tren yang berlaku). Isu konsep hijau dan efisiensi konsumsi energi melalui program Net Zero-Energy Buildings (NZE-Bs) dari sektor perumahan sebagai respon untuk menanggulangi pemanasan global sudah tidak asing di Indonesia, walaupun penerapannya masih belum dapat ditemukan secara signifikan. Konsep hijau yang ditawarkan oleh pengembang perumahan seringkali hanya sebagai trik pemasaran belaka dan tidak diwujudkan serta ditumbuhkan tanggung jawab para penghuni untuk menjaganya. Akibat minimnya pemahaman mengenai konsep hijau tersebut, para pengembang perumahan cenderung lebih banyak menawarkan lingkungan perumahan yang asri dan hijau, bukan konsep hijau yang sebenarnya.Kata Kunci: Sosio-kultur, Efisiensi Energi, Konsumsi energi, Lingkungan, Konsep Hijau